Lá vem os pretos do América: discursividades de mulheres quilombolas sobre os desafios e perspectivas na escolarização da Educação Básica para seus projetos de vida no quilombo do América em Bragança-PA - OLIVEIRA, Kátia Regina Morais de (2023)
This study analyzes the discoursivities of black women and quilombolas on the process of schooling in Basic Education in the community of the Quilombo do América in Bragança-PA. It problematizes the discursivity of black women and quilombolas about the challenges and perspectives in schooling in Basic Education for their life projects. The theoretical framework was based on Lélia Gonzalez, Sueli Carneiro (2020), Angela Davis, Heleieth Saffiot, Bell Hooks, among others for the discussion about black women. For the incursion about the schooling process we dialogue with José Carlos Libâneo, Moacir Gadotti and Dermeval Saviani. For discussions on ethnic-racial relations, we were guided by Lilia Schwarcz, Nilma Gomes, Raquel Amorim Santos, Maria Malcher, among others. Methodologically, the study is a qualitative approach with application of bibliographic and field research. For the generation of the data we used the semi-structured interview with 06 (six) black women and quilombolas about their schooling processes in Basic Education aiming at the challenges and perspectives for their life projects. The analysis was based on the discourse analysis in Bakhtin and his Circle, from the concept of Dialogism. The results of the study show that black women and quilombolas face different and different challenges that contributed to their dropout from school, whether by early pregnancy, obligations with domestic work, care and education of their children, support for the family and also for the impediment of their spouses. In addition, the distance from schools, the financial situation, school curricula disconnected from their ethnic-racial belonging and the need for subsistence were preponderant barriers to dropping out of schooling. Black women and quilombolas face structural racism and discrimination. As a life perspective, these women state that school education is a field where knowledge is acquired, improves their economic conditions through formal work and still contributes to the education of their children. We conclude that the perspective of black women and quilombolas occurs through the belief that education transforms social and economic life, criticality and resistance for the confrontations of daily challenges demarcated by the patriarchy historically established in Brazilian society, structural racism and racial discrimination that remain present in their lives and that leads to their invisibility in Brazilian society. However, his life projects remain alive through his incessant struggles for change, equality, respect, guarantee of rights and the occupation of the most diverse social spaces, including the school.